Time to change: a review of organisational culture change in health care organisations. Issue 3 (5th September 2016) - Johnson, Anya; Nguyen, Helena; Groth, Markus; Wang, Karyn; Ng, Ju Li
Abstract : Purpose: The culture of an organization shapes the attitudes and behaviors of employees and plays a key role in driving organizational outcomes. Yet, it is enormously challenging to manage or change. The purpose of this paper is to review the recent literature on culture change interventions in health care organizations to identify the common themes underpinning these interventions. Design/methodology/approach: The paper is developed from an extensive review of the literature on culture change interventions in health care from 2005 to 2015, building on previous reviews and highlighting examples of good practice. Findings: All culture change interventions included in the review used processes and techniques that can be classified into Lewin's (1951) three stage model of change. These include providing evidence for the need for change through data, a range of successful change strategies, and strategies for embedding the culture change into business as usual. Practical implications: There is no "one size fits all" recipe for culture change. Rather, attention to context with key features including diagnosis and evaluation of culture, a combination of support from leaders and others in the organization, and strategies to embed the culture change are important for the change process to happen. Originality/value: The authors provide an important insight into the key principles and features of culture change interventions to provide practitioners with guidance on the process within health care and other organizations.